A Novel ANO5 Mutation Causing Gnathodiaphyseal Dysplasia With High Bone Turnover Osteosclerosis. (9th September 2016) - Rolvien, Tim; Koehne, Till; Kornak, Uwe; Lehmann, Wolfgang; Amling, Michael; Schinke, Thorsten; Oheim, Ralf
ABSTRACT: Gnathodiaphyseal dysplasia (GDD) is a rare skeletal syndrome that involves an osteopetrosis‐like sclerosis of the long bones and fibrous dysplasia–like cemento‐osseous lesions of the jawbone. Although the genetic analysis of the respective patients has revealed mutations in the ANO5 gene as an underlying cause, there is still no established consensus regarding the bone status of GDD patients. We report a new case of GDD in a 13‐year‐old boy with recurrent diaphyseal fractures of the femur, in whom we identified a novel de novo missense mutation in the ANO5 gene, causing a p.Ser500Phe substitution at the protein level. After confirming the presence of GDD‐characteristic abnormalities within the jaw bones, we focused on a full osteologic assessment using dual‐energy X‐ray absorptiometry (DXA), high‐resolution peripheral quantitative computed tomography (HR‐pQCT), and serum analyses. We thereby identified increased trabecular bone mass accompanied by elevated serum markers of bone formation and bone resorption. The high turnover bone pathology was further confirmed through the analysis of an iliac crest biopsy, where osteoblast and osteoclast indices were remarkably increased. Taken together, our findings provide evidence for a critical and generalized role of anoctamin‐5 (the protein encoded by the ANO5 gene) in skeletal biology. As it is reasonable to speculate that modifying the function of anoctamin‐5 might be useful for therapeutically activating bone remodeling, it is now required to analyze its function at a molecular level, for instance in mouse models. © 2016 American Society for Bone and Mineral Research.